Tracking of physical fitness in elementary school children: The role of changes in body fat - Werneck, André O. [UNESP]; Silva, Danilo R.; Oyeyemi, Adewale L.; Fernandes, Rômulo A. [UNESP]; Romanzini, Marcelo; Cyrino, Edilson S.; de Arruda, Miguel; Ronque, Enio R.V. (Wiley, 2019)
Objectives: The aim of the present study was to examine the stability of physical fitness, and the interrelationships among intra-individual changes in fitness and fatness among elementary school children. Methods: A longitudinal study was conducted among 372 adolescents (196 boys) and followed up over 3 years (from childhood to adolescence). Physical fitness was estimated using three indicators: cardiorespiratory fitness (through a 9-minute running test), flexibility (through a sit-and-reach test), and muscle resistance (through maximal abdominals in 1 minute). Body adiposity was obtained through triceps and subscapular skinfolds. Somatic maturation was assessed by the peak of height velocity. Kappa and Lin's tests of concordance as well as logistic regression analyses were conducted with P < 0.05 in STATA 15.1. Results: Tracking of physical fitness from childhood to adolescence was moderate for both sexes [boys: kappa = 0.441 (P < 0.001); LCCC = 0.591 (P < 0.001). Girls: kappa = 0.335 (P < 0.001); LCCC = 0.534 (P < 0.001)]. A larger increment in body fat was associated with a higher likelihood to decrease a tertile in physical fitness among boys [OR: 4.17 (95% CI: 1.31-13.22)] and with a lower likelihood to increase a tertile in physical fitness among both sexes [boys: OR = 0.25 (95% CI: 0.09-0.67); girls: OR: 0.37 (95% CI: 0.15-0.92)]. Conclusions: Health-related physical fitness has moderate tracking from childhood to adolescence. Increases in body adiposity from childhood to adolescence are associated with a reduction in physical fitness tertile.